The regulatory role of interferon‐γ producing gamma delta T cells via the suppression of T helper 17 cell activity in bleomycin‐induced pulmonary fibrosis. (2nd August 2016) - Segawa, S.; Goto, D.; Iizuka, A.; Kaneko, S.; Yokosawa, M.; Kondo, Y.; Matsumoto, I.; Sumida, T.
Summary: Interstitial pneumonia (IP) is a chronic progressive interstitial lung disease associated with poor prognosis and high mortality. However, the pathogenesis of IP remains to be elucidated. The aim of this study was to clarify the role of pulmonary γδT cells in IP. In wild‐type (WT) mice exposed to bleomycin, pulmonary γδT cells were expanded and produced large amounts of interferon (IFN)‐γ and interleukin (IL)‐17A. Histological and biochemical analyses showed that bleomycin‐induced IP was more severe in T cell receptor (TCR‐δ‐deficient (TCRδ –/– ) mice than WT mice. In TCRδ –/– mice, pulmonary IL‐17A + CD4 + Τ cells expanded at days 7 and 14 after bleomycin exposure. In TCRδ –/– mice infused with γδT cells from WT mice, the number of pulmonary IL‐17A + CD4 + T cells was lower than in TCRδ –/– mice. The examination of IL‐17A –/– TCRδ –/– mice indicated that γδT cells suppressed pulmonary fibrosis through the suppression of IL‐17A + CD4 + T cells. The differentiation of T helper (Th)17 cells was determined in vitro, and CD4 + cells isolated from TCRδ –/– mice showed normal differentiation of Th17 cells compared with WT mice. Th17 cell differentiation was suppressed in the presence of IFN‐γ producing γδT cells in vitro . Pulmonary fibrosis was attenuated by IFN‐γ‐producing γδT cells through the suppression of pulmonary IL‐17A + CD4 + T cells. These results suggested that pulmonary γδT cells seem to play a regulatory role in the development of bleomycin‐induced IP mouse model via the suppression of IL‐17A production.